Efektivitas Layanan Kesehatan Keliling di Papua Terpencil Berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 90 Tahun 2015 - Nora Lelyana; Aris Sarjito (Society, 2024)
Mobile Health Services (MHS) have emerged as a crucial solution to address healthcare disparities in Papua, a region characterized by geographic isolation, inadequate infrastructure, and underserved communities. This study evaluates the effectiveness of MHS in improving access to and the quality of healthcare in remote areas of Papua, guided by Indonesia’s Minister of Health Regulation No. 90 of 2015. Using a qualitative research approach, the study analyzes secondary data from policy documents, implementation reports, and academic literature. The findings reveal that MHS has significantly enhanced access to essential services, including maternal and child health, vaccinations, and primary care, while alleviating travel burdens for isolated populations. However, the quality of care remains inconsistent due to resource limitations, workforce shortages, and inadequate medical equipment. Additional challenges, such as cultural barriers, logistical complexities, and financial instability, hinder the long-term sustainability of these services. Key strategies to address these issues include securing stable funding, enhancing workforce capacity, leveraging digital technologies, and fostering community engagement. Despite notable progress, systemic challenges must be addressed to ensure sustainable and equitable healthcare delivery in Papua.